Structures of Qβ virions, virus-like particles, and the Qβ–MurA complex reveal internal coat proteins and the mechanism of host lysis - Cui, Zhicheng; Gorzelnik, Karl V.; Chang, Jeng-Yih; Langlais, Carrie; Jakana, Joanita; Young, Ry; Zhang, Junjie (Proceedings of the National Academy of Sciences - PNAS, 2017)
In single-stranded RNA bacteriophages (ssRNA phages) a single copy of the maturation protein binds the genomic RNA (gRNA) and is required for attachment of the phage to the host pilus. For the canonical Allolevivirus Qβ the maturation protein, A₂, has an additional role as the lysis protein, by its ability to bind and inhibit MurA, which is involved in peptidoglycan biosynthesis. Here, we determined structures of Qβ virions, virus-like particles, and the Qβ–MurA complex using single-particle cryoelectron microscopy, at 4.7-Å, 3.3-Å, and 6.1-Å resolutions, respectively. We identified the outer surface of the β-region in A₂ as the MurA-binding interface. Moreover, the pattern of MurA mutations that block Qβ lysis and the conformational changes of MurA that facilitate A₂ binding were found to be due to the intimate fit between A₂ and the region encompassing the closed catalytic cleft of substrate-liganded MurA. Additionally, by comparing the Qβ virion with Qβ virus-like particles that lack a maturation protein, we observed a structural rearrangement in the capsid coat proteins that is required to package the viral gRNA in its dominant conformation. Unexpectedly, we found a coat protein dimer sequestered in the interior of the virion. This coat protein dimer binds to the gRNA and interacts with the buried α-region of A₂, suggesting that it is sequestered during the early stage of capsid formation to promote the gRNA condensation required for genome packaging. These internalized coat proteins are the most asymmetrically arranged major capsid proteins yet observed in virus structures.